Human Embryonic Stem Cell-Derived Neural Lineages as In Vitro Models for Screening the Neuroprotective Properties of Lignosus rhinocerus (Cooke) Ryvarden. (19th August 2019) - Yeo, Yin; Tan, Joash Ban Lee; Lim, Lee Wei; Tan, Kuan Onn; Heng, Boon Chin; Lim, Wei Ling
Abstract : In the biomedical field, there is growing interest in using human stem cell-derived neurons as in vitro models for pharmacological and toxicological screening of bioactive compounds extracted from natural products. Lignosus rhinocerus (Tiger Milk Mushroom) is used by indigenous communities in Malaysia as a traditional medicine to treat various diseases. The sclerotium of L. rhinocerus has been reported to have medicinal properties, including various bioactivities such as neuritogenic, anti-inflammatory, and anticancer effects. This study aims to investigate the neuroprotective activities of L. rhinocerus sclerotial extracts. Human embryonic stem cell (hESC)-derived neural lineages exposed to the synthetic glucocorticoid, dexamethasone (DEX), were used as the in vitro models. Excess glucocorticoids have been shown to adversely affect fetal brain development and impair differentiation of neural progenitor cells. Screening of different L. rhinocerus sclerotial extracts and DEX on the hESC-derived neural lineages was conducted using cell viability and neurite outgrowth assays. The neuroprotective effects of L. rhinocerus sclerotial extracts against DEX were further evaluated using apoptosis assays and Western blot analysis. Hot aqueous and methanol extracts of L. rhinocerus sclerotium promoted neurite outgrowth of hESC-derived neural stem cells (NSCs) with negligible cytotoxicity. Treatment with DEX decreased viability of NSCs by inducing apoptosis. Coincubation of L. rhinocerus methanol extract with DEX attenuated the DEX-induced apoptosis and reduction in phospho-Akt (pAkt) level in NSCs. These results suggest the involvement of Akt signaling in the neuroprotection of L. rhinocerus methanol extract against DEX-induced apoptosis in NSCs. Methanol extract of L. rhinocerus sclerotium exhibited potential neuroprotective activities against DEX-induced toxicity in hESC-derived NSCs. This study thus validates the use of human stem cell-derived neural lineages as potential in vitro models for screening of natural products with neuroprotective properties.